Integrated metabolome and transcriptome analyses of anthocyanin biosynthesis reveal key candidate genes involved in colour variation of Scutellaria baicalensis flowers - Fengdan Guo; Renwei Guan; Xinru Sun; Cuicui Zhang; Chenggang Shan; Mengyu Liu; Ning Cui; Ping Wang; Huibin Lin (BMC Plant Biology, 2023)
Abstract Background Bright flower colour assists plants attract insects to complete pollination and provides distinct ornamental values. In some medicinal plants, diverse flower colour variations usually imply differences in active ingredients. Compared to the common bluish purple of Scutellaria baicalensis flower (SB), the natural variants present rose red (SR) and white (SW) flowers were screened out under the same growing conditions in the genuine producing area Shandong Province, China. However, the mechanism of flower colour variation in S. baicalensis was remain unclear. In the present study, we conducted integrated transcriptome and metabolome analyses to uncover the metabolic difference and regulation mechanism in three S. baicalensis flowers. Results The results showed that 9 anthocyanins were identified. Among which, 4 delphinidin-based anthocyanins were only detected in SB, 4 cyanidin-based anthocyanins (without cyanidin-3-O-glucoside) mainly accumulated in SR, and no anthocyanin but high level of flavanone, naringenin, was detected in SW. The gene expression profile indicated that the key structural genes in the flavonoid and anthocyanin biosynthesis pathway differentially expressed in flowers with different colours. Compared to SB, the down-regulated expression of F3’5’H, ANS, and 3GT gene in SR might influence the anthocyanin composition. Especially the InDel site with deletion of 7 nucleotides (AATAGAG) in F3’5’H in SR might be the determinant for lack of delphinidin-based anthocyanins in rose red flowers. In SW, the lower expression levels of DFR and two F3H genes might reduce the anthocyanin accumulation. Notably the SNP site of G > A mutation in the splicing site of DFR in SW might block anthocyanin biosynthesis from flavanones and thus cause white flowers. In addition, several key transcription factors, including MYB, bHLH, and NAC, which highly correlated with structural gene expression and anthocyanin contents were also identified. Conclusions These results provide clues to uncover the molecular regulatory mechanism of flower colour variation in S. baicalensis and promote novel insights into understanding the anthocyanin biosynthesis and regulation.